Impact of the endocrine disruptor methoxychlor on the survival and glycolytic metabolism of Sertoli cells - Bordadágua, Mariana Costa (2023)
Endocrine-disrupting chemicals (EDCs) are manufactured or natural compounds that are capable of interfering with normal endocrine function and, consequently, with the body homeostasis. The EDC methoxychlor (MXC) is an organochloride pesticide and a xenoestrogen with moderate persistence in the environment, capable of adversely affecting spermatogenesis, deregulating the development of germ cells, and interfering with sperm function. However, a knowledge gap exists regarding the impact of MXC on other testicular cell types, namely, Sertoli cells (SCs), the somatic testicular cells within the seminiferous tubules. SCs physically and metabolically sustain germ cell survival, and any dysregulation induced by EDC action affects the spermatogenic output. The present dissertation investigated the effect of the EDC MXC on the survival and glycolytic metabolism of SCs, as well as their fatty acid uptake. For this purpose, primary SCs were isolated from 4-month-old rats and maintained in culture for 48 h in the presence (25 and 100 µM) or in the absence (control) of MXC. SCs’ survival and apoptotic rate were evaluated by trypan blue exclusion and spectrophotometrically, respectively. Glucose and fatty acid consumption, lactate production, and the expression of key regulators of the glycolytic pathway were measured by spectrophotometric assays and Western blot analyses. The results obtained demonstrated that both 25 and 100 µM MXC decreased the viability of SCs, accompanied by increased caspase-3-like activity, in a concentrationdependent manner. Enhanced glucose consumption and lactate production were also observed upon MXC exposure (25 and 100 µM). Given these results, we focused our metabolic intervenients analysis on the lowest MXC concentration. These observations were underpinned by the augmented expression levels of glucose transporter 3, and phosphofructokinase 1, and expression levels and activity of lactate dehydrogenase. In addition, 25 µM MXC increased fatty acid consumption by SCs. These findings demonstrated that MXC has an impact on the metabolic characteristics of SCs, which is a novel perspective on the effects of EDCs leading to male infertility. Further studies should be performed to identify other dysregulated molecules or susceptible metabolic pathways, which could help develop therapeutical and/or preventive strategies for male infertility.